Artificial oxygen carriers as a possible alternative to red cells in clinical practice - Barbosa, Fabiano Timbó; Jucá, Mário Jorge; Castro, Aldemar Araujo; Duarte, José Lira; Barbosa, Luciano Timbó (São Paulo Medical Journal, 2009)
Fluid resuscitation is intended to eliminate microcirculatory disorders and restore adequate tissue oxygenation. The safety limits for a restrictive transfusion policy are given by patients’ individual tolerance of acute normovolemic anemia. Artificial oxygen carriers based on perfluorocarbon or hemoglobin are attractive alternatives to allogenic red blood cells. There are many risks involved in allogenic blood transfusions and they include transmission of infections, delayed postoperative wound healing, transfusion reactions, immunomodulation and cancer recurrence. Regardless of whether artificial oxygen carriers are available for routine clinical use, further studies are needed in order to show the safety and efficacy of these substances for clinical practice.